2013
DOI: 10.1080/13527258.2011.651740
|View full text |Cite
|
Sign up to set email alerts
|

Heritage, health and well-being: assessing the impact of a heritage focused intervention on health and well-being

Abstract: Notes on contributors:Erica Ander is Research Assistant on the UCL Heritage in Hospitals research project. She also works as a museum and heritage consultant specialising in visitor studies and audience research. Her research interests include qualitative methodologies to capture cultural outcomes and health and wellbeing issues in the museum sector. Here we present key findings from a qualitative evaluation of a heritage focused intervention carried out in a range of health care settings. The aim of the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 3 publications
2
52
0
Order By: Relevance
“…It can be argued that opportunity for meaning-making in healthcare settings plays a vital role in adjusting to illness and other stressful events (Park, 2010). The hospital context can entail a loss of personal attributes and individuality, with periods of boredom, introspection and illness or diagnosis dominating an individual's personality (Ander et al, 2012;Watkins, 1997). The facility in the sessions for participants to share memories and personal qualities from other parts of their lives may bestow benefit to the individual and enhance communication and understanding with staff (Ander et al, 2013).…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be argued that opportunity for meaning-making in healthcare settings plays a vital role in adjusting to illness and other stressful events (Park, 2010). The hospital context can entail a loss of personal attributes and individuality, with periods of boredom, introspection and illness or diagnosis dominating an individual's personality (Ander et al, 2012;Watkins, 1997). The facility in the sessions for participants to share memories and personal qualities from other parts of their lives may bestow benefit to the individual and enhance communication and understanding with staff (Ander et al, 2013).…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
“…Paddon, Thomson, Menon, Lanceley and Chatterjee (2013) noted that thinking and meaning making opportunities were utilised by hospital patients participating in museum object handling sessions in conjunction with significantly enhanced measures of happiness and wellbeing. Ander et al (2012) used grounded theory to analyse museum object handling sessions carried out with a range of healthcare participants, identifying key outcomes termed "engagement processes" such as learning about objects and "expressions of wellbeing" such as eliciting memories leading to a renewed sense of identity (p. 234). A qualitative study carried out by Ander et al (2013) on the impact of object handling in two healthcare settings, neurological rehabilitation and inpatient mental health highlighted eight themes contributing to the success of the sessions, including enhanced conversational and social skills and enjoyment.…”
Section: Research Into Museum Object Handling Sessionsmentioning
confidence: 99%
“…7 in a study of 300 hospital patients and care home residents, a mixed-methods framework was used to assess the impact of 30-40 min museum object handling sessions on participants, using pre-post session measures of psychological and subjective wellbeing alongside qualitative analysis of session recordings. [8][9][10][11] Quantitative measures showed significant increases in participant wellness and happiness scores. [8][9][10] Qualitative analysis revealed that patients 'used the heritage objects combined with tailored and easy social interaction, sensory stimulus and learning opportunities to tap into concerns about identity, emotions, energy levels and motivation' (pp.…”
mentioning
confidence: 99%
“…[8][9][10] Qualitative analysis revealed that patients 'used the heritage objects combined with tailored and easy social interaction, sensory stimulus and learning opportunities to tap into concerns about identity, emotions, energy levels and motivation' (pp. [8][9][10][11][12]. 11 in a mixedmethods study using a pre-post design within an art gallery, outcomes showed that viewing and making art by people with dementia had an impact on episodic memory and verbal fluency.…”
mentioning
confidence: 99%
See 1 more Smart Citation